Regular embeddings of cycles with multiple edges revisited - Hu, Kan (Ars mathematica contemporanea, 2015)
Regular embeddings of cycles with multiple edges have been reappearing in the literature for quite some time, both in and outside topological graph theory. The present paper aims to draw a complete picture of these maps by providing a detailed description, classification, and enumeration of regular embeddings of cycles with multiple edges on both orientable and non-orientable surfaces. Most of the results have been known in one form or another, but here they are presented from a unique viewpoint based on finite group theory. Our approach brings additional information about both the maps and their automorphism groups, and also gives extra insight into their relationships.
Keywords: Hölderjev izrek; Hölder's Theorem; Möbius map; Möbiusov zemljevid; multiple edge; regular embedding; regularna vložitev; večkratna povezava